Embodied Carbon in Australian Residential Houses: A Preliminary Study - Chethana Illankoon; Sadith Chinthaka Vithanage; Nethmin Malshani Pilanawithana (Buildings, 2023)
Embodied carbon is a buzzword in the construction industry. Australia is committed to achieving Net Zero 2050 targets, and minimizing embodied carbon (EC) is inevitable. Owing to the population growth, there will be a significant demand for residential construction. Therefore, the material consumption in residential construction should be evaluated and proper strategies should be in place to minimize EC. The aim of this research is to undertake a preliminary study of EC in the Australian residential sector, with an emphasis on new residential home construction. This research presents a preliminary study on EC in residential buildings in Australia. Three case study residential buildings were used in this study. All three case studies are single -story residential units, with a gross floor area between 200 and 240 m2. One Click LCA software was used to calculate the EC. The EC of three case study residential homes is between 193 and 233 kgCO2e/m2. Based on the findings of this study, ‘other structures and materials’ contribute to a large amount of EC in residential construction. Concrete and aluminum are considered significant contributors to EC. Therefore, it is vital to either introduce low-EC material to replace aluminum windows or introduce various design options to minimize the use of aluminum in windows. There are various sustainable concretes available with low EC. It is essential to explore these low-EC concretes in residential homes as well. This research identifies the importance of adopting strategies to reduce the carbon impact from other sources, including concrete. It is also essential to consider the EC through transportation related to construction and promote locally sourced building materials in residential construction. Therefore, the results of this research indicate the necessity of reducing raw material consumption in Australian residential construction by implementing approaches such as a circular economy in order to circulate building materials throughout the construction supply chain and reduce raw material extraction.